2014
DOI: 10.1111/1346-8138.12391
|View full text |Cite
|
Sign up to set email alerts
|

Atypical mycobacterial cutaneous infections in Egyptians: A clinicopathological study

Abstract: Atypical mycobacteria comprise an uncommon heterogenous non-tuberculous group of acid-fast bacteria that rarely involve skin. The pattern of atypical mycobacterial cutaneous infections (AMCI) has not been previously studied in Egypt. The aim of this study was to describe the clinical characteristics, pathological features and species profile of AMCI among Egyptian patients. A retrospective study included 46 cases, diagnosed with AMCI during the period 2002 to 2012. The study included 34 males (73.9%) and 12 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
4
13
0
Order By: Relevance
“…The most frequent NTM involved in cutaneous infections are M. fortuitum , M. avium , M. gordonae , M. chelonae , M. abscessus , M. kansasii , M. leprae and M. ulcerans (Aboutalebi et al , 2012; Bhambri et al , 2009; El-Khalawany, 2014; Liao et al , 2007; Böddinghaus et al , 2007; Ridley & Jopling, 1966), with lesions generally localized in the upper limbs and peripheral parts of the body, where the lower body temperature matches well with their optimal growth temperature, as classically highlighted for M. marinum infections (Patel et al , 2014; Tebruegge & Curtis, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The most frequent NTM involved in cutaneous infections are M. fortuitum , M. avium , M. gordonae , M. chelonae , M. abscessus , M. kansasii , M. leprae and M. ulcerans (Aboutalebi et al , 2012; Bhambri et al , 2009; El-Khalawany, 2014; Liao et al , 2007; Böddinghaus et al , 2007; Ridley & Jopling, 1966), with lesions generally localized in the upper limbs and peripheral parts of the body, where the lower body temperature matches well with their optimal growth temperature, as classically highlighted for M. marinum infections (Patel et al , 2014; Tebruegge & Curtis, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, several studies were conducted regarding the burden of M. tuberculosis, its genetic diversity, and drug resistance to antimycobacterial drugs in Egypt [ 12 , 13 , 14 , 15 ]. However, very few studies have reported the clinical existence of NTM in Egypt [ 16 , 17 ]. The resemblance of the clinical presentation of NTM to the well-established TB presents a tough challenge in diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our entire cohort, eight patients had recurrence of their disease, of which half experienced full recovery and half were lost 14 3…”
Section: Treatment Datamentioning
confidence: 97%